Forced Remediation: The Use of Corporate Monitors in Sanctions for Misconduct - Files, Rebecca L.; Martin, Gerald S.; Sun, Yan (The Accounting Review, 2025)
ABSTRACT Following securities law violations, regulators can require firms to hire a corporate monitor to implement reforms that limit future misconduct and protect investors. We examine the determinants of including a corporate monitor as equitable relief in an enforcement action, as well as their effectiveness in promoting positive change at a firm. Using a structural equation model that jointly determines monetary and nonmonetary sanctions, we find that monitor assignments are related to the nature of the offense, violation severity, and investor harm. We also find that monitors with targeted accounting oversight responsibilities are associated with improved corporate culture, a higher likelihood of financial restatements during their tenure, and enhanced financial reporting credibility at the firms they oversee relative to enforcement firms without such monitors. Although corporate monitors can foster positive change, their impact depends on the scope of their responsibilities. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: K22; M14; M41; M42; M48.